Hubungan Antara Activity Of Daily Living (ADL) dengan Kualitas Hidup pada Lansia di Komunitas Binaan Pusaka 41 Yayasan Al - Madiniyah Jakarta Barat - Adimas Muhammad Fachreza Danuputra; Marcella Erwina Rumawas (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2021)
. Activity of Daily Living (ADL) is often used to measure individual independence in carrying out activities and functions of daily life. Whilst quality of life is the view of each individual related to his position in life, the value system in which they are located and their relationship to life goals, expectations, standards of living and other related aspects. According to WHO, the quality of life includes fours aspects, namely physical health, mental health, social and environmental. Elderly are individuals aged 60 years and over, and are a population group at risk. In Indonesia, research on ADL and quality of life in elderly is still very limited. This cross-sectional observational analytic study was aimed to determine the relationship between ADL and quality of life qmong the elderly living in the community of Pusaka 41 Al – Madiniyah Foundation, West Jakarta. A total of 40 respondents were selected by consecutive non–random sampling method, data were collected through interview using ADL and WHOQOL-BREF questionnaires and analyzed using correlation statistical test. Of the 40 respondents, the mean score of ADL was 18,5 (SD=1,7) and the mean quality of life score was 65,4 (SD=12,2) with the highest score on the social aspect 68,4 (SD=18,6) and the lowest one on the physical health aspect of 63,1 (SD=13,2). In this study, there was a weak but not statistically significant correlation between ADL and quality of life (r=0,02; p-value=0,93). Further research with larger and random sample is needed to confirm the relationship between ADL and quality of life in the elderly. Keyword: Activity of Daily Living, quality of life, elderly, WHOQOL-BREF.